2005
DOI: 10.1007/s11194-005-5062-3
|View full text |Cite
|
Sign up to set email alerts
|

Violent Juvenile Sex Offenders Compared with Violent Juvenile Nonsex Offenders: Explorative Findings From the Pittsburgh Youth Study

Abstract: Only a limited number of studies have compared the psychosocial characteristicsSince the recognition in the 1970's and 1980's that juveniles are capable of committing sex offenses, many studies have investigated this problem. However, many methodological shortcomings were inherent to these studies, including small sample size, biased sampling, nonstandardized instruments and a reliance on

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(37 citation statements)
references
References 38 publications
0
36
1
Order By: Relevance
“…The low mean score of the scale “problems with self esteem” hints (according to the test's manual) toward a minimal awareness of the ASOs of their problems. The lack of intergroup differences observed in the internalizing scales can be explained by the small number of boys with sexual offenses against children in this study because it has been reported that internalizing behavior problems are in particular associated with sexual offending against children, and externalizing behavior problems with sexual offending against peers/adults . The overall low mean values could once again be ascribed to the early, unselective investigation that was applied to the juveniles in this study, as other studies with nonclinical, self‐reported sexually offending students found little psychopathology as well (Finkelhor 1988 and Fromuth 1991 as cited by ).…”
Section: Discussionmentioning
confidence: 50%
“…The low mean score of the scale “problems with self esteem” hints (according to the test's manual) toward a minimal awareness of the ASOs of their problems. The lack of intergroup differences observed in the internalizing scales can be explained by the small number of boys with sexual offenses against children in this study because it has been reported that internalizing behavior problems are in particular associated with sexual offending against children, and externalizing behavior problems with sexual offending against peers/adults . The overall low mean values could once again be ascribed to the early, unselective investigation that was applied to the juveniles in this study, as other studies with nonclinical, self‐reported sexually offending students found little psychopathology as well (Finkelhor 1988 and Fromuth 1991 as cited by ).…”
Section: Discussionmentioning
confidence: 50%
“…Of the 5 studies reporting on ethnicity, 2 studies found Caucasians to be more prevalent in the group of sex offenders (Veneziano et al, 2004;van Wijk, van Horn, et al, 2005). In the remaining 3 studies, no differences were found between groups on race (Bischof et al, 1995;van Wijk et al, 2004;van Wijk, Loeber, et al, 2005). With regard to family socioeconomic status, parental employment, and educational status, 4 studies did not find differences between sex offenders and non-sex offenders (Bischof et al, 1995;Butler & Seto, 2002;Ford & Linney, 1995;van Wijk, Loeber, et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…All but 3 (18%) studies used a cross-sectional design. Exceptions were 2 studies (Hagan, Gust-Brey, Cho, & Dow, 2001;Sipe, Jensen, & Everett, 1998) in which juvenile offenders were continually followed into adulthood and one Veneziano, LeGrand, and Richards (2004) van Wijk, Vreugdenhil, and Bullens (2004) van Wijk, van Horn, Bullens, Bijleveld, and Doreleijers (2005) van Wijk, Loeber, et al (2005) 78 longitudinal study in which juvenile sex offenders were followed within a normal population sample (van Wijk, Loeber, et al, 2005). Structured interview methods, questionnaires, or psychological tests were most frequently used for collecting information.…”
Section: Resultsmentioning
confidence: 99%
“…Data from another longitudinal study focused on general delinquency have been used to determine the extent to which youth who ultimately committed violent offenses differed from youth who did not and also, to attempt to differentiate youth who ultimately committed violent sexual offenses from youth who ultimately committed violent nonsexual offenses (van Wijk et al, 2005). In this study, violent and nonviolent groups differed significantly on 54 of the 66 (81%) risk factors examined, including factors pertaining to delinquency, substance use, emotional/behavior problems, sexual behavior, attitudes, competence, family factors, and demographic factors.…”
Section: Preventing the Onset Of Csa Perpetration: An Adolescent-focumentioning
confidence: 99%